GAYA HIDUP KONSUMSI FASHION MAHASISWA UNIVERSITAS SRIWIJAYA ASAL KABUPATEN MUARA ENIM - Vhonita, Ussy; Purnama, Dadang Hikmah (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2023)
This research examines the